Spatial-temporal variability of metal pollution across an industrial district, evidencing the environmental inequality in São Paulo. (August 2020) - Locosselli, Giuliano Maselli; Moreira, Tiana Carla Lopes; Chacón-Madrid, Katherine; Arruda, Marco Aurélio Zezzi; Camargo, Evelyn Pereira de; Kamigauti, Leonardo Yoshiaki; da Trindade, Ricardo Ivan Ferreira; Andrade, Maria de Fátima; André, Carmen Diva Saldiva de; André, Paulo Afonso de; Singer, Julio M.; Saiki, Mitiko; et al.
Abstract: Although air pollution decreased in some cities that shifted from an industrial to a service-based economy, and vehicular emission regulation became more restrictive, it is still a major risk factor for mortality worldwide. In central São Paulo, Brazil, air quality monitoring stations and tree-ring analyses revealed a decreasing trend in the concentrations of particulate matter and metals. Such trends, however, may not be observed in industrial districts located in the urban periphery, where the usual mobile sources may be combined with local stationary sources. To evaluate environmental pollution in an industrial district in southeastern São Paulo, we assessed its spatial variability, by measuring magnetic properties and concentrations of Al, Ba, Ca, Cl, Cu, Fe, K, Mg, Mn, P, S, Sr, Zn in the bark of 62 trees, and its temporal trends, by measuring Cd, Cu, Ni, Pb, V, Zn in tree rings of three trees. Source apportionment analysis based on tree barks revealed two clusters with high concentrations of metals, one related to vehicular and industrial emissions (Al, Ba, Cu, Fe, Zn) in the east side of the industrial cluster, and the other related to soil resuspension (Cu, Zn, Mn) in its west side. These patterns are also supported by the magnetic properties of bark associated with iron oxides and titanium-iron alloy concentrations. Dendrochemical analyses revealed that only the concentrations of Pb consistently decreased over the last four decades. The concentrations of Cd, Cu, Ni, V, and Zn did not significantly decrease over time, in contrast with their negative trends previously reported in central São Paulo. This combined biomonitoring approach revealed spatial clusters of metal concentration in the vicinity of this industrial cluster and showed that the local population has not benefited from the decreasing polluting metal concentrations in the last decades. Graphical abstract: Image 1 Highlights: Previous studies show decreasing trend in metal pollution in central São Paulo. Such decreasing trends is not fully observed, but for Pb, in an industrial district. Increasing V was observed in the part of the district under industrial emission. The population of this district is exposure to mixed sources of air pollution. Tree barks and tree rings can be used together to assess pollution from stationary sources.